2020
DOI: 10.24251/hicss.2020.086
|View full text |Cite
|
Sign up to set email alerts
|

How Game Features Give Rise to Altruism and Collective Action? Implications for Cultivating Cooperation by Gamification

Abstract: Due to the general gamification of our culture and society as well as the proliferation of games in our everyday activities, people are increasingly looking at games and gamification as a source for cooperation and other prosocial behaviors. However, not all game features lead to increased cohesion, cooperation or collaboration between people. While some games indeed are geared for cooperation, majority of games also aim toward competition or just non-social activity. Therefore, a prominent research problem ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 55 publications
5
29
2
Order By: Relevance
“…The COVID-19 pandemic does not seem to have a significant effect on the raiding activity, even though it might be possible that as spring arrived in the observed municipality, the better outdoor weather had an opposing impact to the self-isolation recommendation related to COVID-19, and increased players' motivation to play. As we are concerned in particular with how government-issued restrictions impacted raiding activity, we focus on the time period of five days before (12)(13)(14)(15)(16) the Finnish government's intervention and five days afterwards (18)(19)(20)(21)(22). In the time period, five days before the limitations were issued there were 79 raids with seven containing more than 10 people, and in the time period five days after we recorded 70 raids with eight containing more than 10 people.…”
Section: Results On Observation Of Social-play During the Covid-19 Pandemicmentioning
confidence: 99%
See 3 more Smart Citations
“…The COVID-19 pandemic does not seem to have a significant effect on the raiding activity, even though it might be possible that as spring arrived in the observed municipality, the better outdoor weather had an opposing impact to the self-isolation recommendation related to COVID-19, and increased players' motivation to play. As we are concerned in particular with how government-issued restrictions impacted raiding activity, we focus on the time period of five days before (12)(13)(14)(15)(16) the Finnish government's intervention and five days afterwards (18)(19)(20)(21)(22). In the time period, five days before the limitations were issued there were 79 raids with seven containing more than 10 people, and in the time period five days after we recorded 70 raids with eight containing more than 10 people.…”
Section: Results On Observation Of Social-play During the Covid-19 Pandemicmentioning
confidence: 99%
“…While Riar et al [21] found a correlation between engaging with cooperative game features and altruism, this finding can also be explained by the fact that, in Ingress, players face a strong opposing force, other human players, making cooperation necessary for individual and the team's success [25]. Furthermore, LBG teams have been shown to impact players' language adaption [25], proving the impact of social influence on player behaviour.…”
Section: How Location-based Games Influence Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…6, 32] and in numerous leisure applications, perhaps most prominently in games [e.g. 17,29,30,37,43]. Due to the now seemingly extensive familiarity with the technology, perhaps we have reached a stage in which we need to reconsider what novelty stands for in AR and on the basis of what technological virtues or alternative proficiencies we operationalize novelty in future AR-based research.…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%